Karakterisasi Ekstrak Etanolik Daun Asam Jawa (Tamarindus indica L.) - Munim, Abdul; Hanani, Endang; Rahmadiah, Rahmadiah (UI Scholars Hub, 2009)
Leaves of tamarind (Tamarindus indica L.) has been traditionally used to treat some diseases such as: constipation, dyspepsia, flatulence and urinary tract infection. The leaves extract also reported has antibacterial and antidiabetic activities. It is essential to determine its specific and non specific parameters in assesing the quality and safety. The samples collected from three different perferctures. Grounded samples were macerated with ethanol. The extracts were subjected to determine its characteristic parameters. Parameter of quality for the extracts consisted of water content, ethanol-extractive, water-extractive, loss on drying, total ash, acid-insoluble ash, solvent residue and heavy metal content. Phytochemical identification showed that the ex-tract contains flanovoid, tannin, glycosides, and saponin. TLC chromatogram using chloroform-methanol-water (80:12:2) as mobile phase, exhibited 4 spots after sprayed with iron(III) chloride. Total phenolic was determined pectrophotometrically using Folin Ciocalteu reagent, gave 0.35-8.24% total phenolic as gallic acid.